PENGARUH BUZZER MARKETING DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN SKINCARE DAVIENA (Studi Pada Mahasiswa Program Studi Manajemen Angkatan 2021 UBP Karawang) - Akmaliyah, Siti Sa'adah; Suherman, Enjang; Khalida, Laras Ratu (JURNAL ADMINISTRASI & MANAJEMEN, 2025)
This study aims to examine the influence of buzzer marketing and brand trust on purchasing decisions for Daviena Skincare products by students of the Management Research Program Class of 2021, Universitas Buana Perjuangan Karawang. The focus of this study includes buzzer marketing activities on social media and excessive claims from Daviena that have the potential to damage customer trust. The research method used is quantitative with a survey technique through a Likert scale-based questionnaire, involving 100 respondents selected by purposive sampling. Data analysis used multiple linear regression. The results of the study showed that buzzer marketing had a moderate effect on purchasing decisions, while brand trust had a stronger and more significant effect. Simultaneously, these two variables were proven to influence purchasing decisions for Daviena Skincare products. These findings indicate that in the competitive skincare industry, effective buzzer marketing strategies and efforts to build brand trust can increase consumer purchasing interest. Therefore, companies are advised to maintain customer trust while continuing to utilize social media positively.